Liposomal drug delivery systems for targeted cancer therapy: is active targeting the best choice?. (November 2016) - Fathi, Shaghayegh; Oyelere, Adegboyega K
Liposomes are biodegradable and biocompatible self-forming spherical lipid bilayer vesicles. They can encapsulate and deliver one or more hydrophobic and hydrophilic therapeutic agents with poor therapeutic indices to tumor sites. Properties such as lipid bilayer fluidity, charge, size and surface hydration can be modified to extend liposome circulation time in the bloodstream and enhance efficacy. The focus of this review is on ligand-conjugated liposomes and their potential application in tumor-targeted delivery. Ligand-conjugated liposomes are designed to target receptors which are overexpressed on tumor cells to decrease drugs side effects by enhancing their selective delivery to tumor site. Despite the extensive research in this area, no small molecule ligand-conjugated liposome has been approved up to date for cancer therapy.